2022
DOI: 10.3390/ijms231911270
|View full text |Cite
|
Sign up to set email alerts
|

Antibiofilm Properties of Antiseptic Agents Used on Pseudomonas aeruginosa Isolated from Diabetic Foot Ulcers

Abstract: In diabetic foot ulcers (DFUs), biofilm formation is a major challenge that promotes wound chronicity and delays healing. Antiseptics have been proposed to combat biofilms in the management of DFUs. However, there is limited evidence on the activity of these agents against biofilms, and there are questions as to which agents have the best efficiency. Here, we evaluated the antibiofilm activity of sodium hypochlorite, polyvinylpyrrolidoneIodine (PVPI), polyhexamethylenebiguanide (PHMB) and octenidine against Ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…The aim of the study was to compare the efficacy of low hypochlorite-containing solutions vs. polyhexanide-containing antiseptic. The reason behind this agenda was the contradictory results concerning the antimicrobial (including antibiofilm) potential of these earlier antiseptics ( Barrigah-Benissan et al., 2022 ; Severing et al., 2022 ). The inclusion of the polyhexanide-base antiseptic, served as the control setting of experiments because antimicrobial/antibiofilm potential of PHMB is generally accepted and recognized in the in vitro and clinical studies) ( To et al., 2016 ; Kramer et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the study was to compare the efficacy of low hypochlorite-containing solutions vs. polyhexanide-containing antiseptic. The reason behind this agenda was the contradictory results concerning the antimicrobial (including antibiofilm) potential of these earlier antiseptics ( Barrigah-Benissan et al., 2022 ; Severing et al., 2022 ). The inclusion of the polyhexanide-base antiseptic, served as the control setting of experiments because antimicrobial/antibiofilm potential of PHMB is generally accepted and recognized in the in vitro and clinical studies) ( To et al., 2016 ; Kramer et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our practice, we use a solution of sodium hypochlorite/hypochlorous acid <0.08% (NaOCl/HOCl). The NaOCl has been proven in vitro to have efficiency against the biofilm formed by Staphylococcus aureus (SA), Staphylococcus epidermidis (SE), Pseudomonas aeruginosa (PA) and other wound pathogens, which are commonly encountered in DSWI 2,16,17 . As described in 1915 by Henry Drysdale Dakin, the Dakin solution classically contains 0.5% buffered sodium hypochlorite 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The NaOCl has been proven in vitro to have efficiency against the biofilm formed by Staphylococcus aureus (SA), Staphylococcus epidermidis (SE), Pseudomonas aeruginosa (PA) and other wound pathogens, which are commonly encountered in DSWI. 2 , 16 , 17 As described in 1915 by Henry Drysdale Dakin, the Dakin solution classically contains 0.5% buffered sodium hypochlorite. 18 As the active ingredients in this solution can have a toxic effect on different cells like fibroblasts, macrophages, or stratum corneum, lower doses of this antiseptic solution need to be used in open wounds, as the toxicity appears to be dose‐related.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have demonstrated efficacy of PHMB on a Gram-negative bacteria and Gram-positive bacteria, [43][44][45][46][47] fungi, [48][49][50] certain viruses, 51,52 and single-celled parasites (amoeba). 53,54 PHMB has also been shown to show antibiofilm activity on biofilms, 31,47,48,[55][56][57][58] including wound biofilms.…”
Section: Experimental Assessment Of Anti-biofilm Activitymentioning
confidence: 99%
“…In vitro studies have demonstrated efficacy of PHMB on a Gram-negative bacteria and Gram-positive bacteria, [43][44][45][46][47] fungi, [48][49][50] certain viruses, 51,52 and single-celled parasites (amoeba). 53,54 PHMB has also been shown to show antibiofilm activity on biofilms, 31,47,48,[55][56][57][58] including wound biofilms. 59,60 Octenidine has also been demonstrated to have antibiofilm activity in in vitro biofilm model assays, 61 and a number of studies have shown HOCl to exhibit antibiofilm activity.…”
Section: Experimental Assessment Of Anti-biofilm Activitymentioning
confidence: 99%